Relationships Between Aerobic and Anaerobic Parameters With Game Technical Performance in Elite Goalball Athletes - Alves, Isabella dos Santos; Kalva-Filho, Carlos Augusto; Aquino, Rodrigo; Travitzki, Leonardo; Tosim, Alessandro; Papoti, Marcelo; Morato, Márcio Pereira (Frontiers in Physiology, 2018)
Abstract Our aims were to compare physiological parameters from the laboratory environment and simulated goalball games, test relationships between physiological parameters in the laboratory and game technical performance, and examine the associations between physiological and technical responses during games. Seven elite athletes from the Brazilian National Team performed in the laboratory; i) an incremental test to determine peak oxygen consumption, its corresponding speed, and peak blood lactate concentration, and ii) submaximal and supramaximal efforts to estimate maximal anaerobic contribution. Simulated games were also performed to determine physiological responses throughout the game, and to analyze the game technical performance (number of throws, defenses, recovery, and density of actions). No correlations (unclear) were found between laboratory and games analyses for peak oxygen consumption [47.3 (17.2) vs. 25.8 (18.2) mL•Kg-1•min-1], peak blood lactate concentrations [10.2 (5.4) vs. 2.0 (0.7) mM], and total anaerobic contribution [21.0 (14.0) vs. 4.8 (6.1) mL.Kg-1]. Peak oxygen consumption in the laboratory condition presented very likely correlations with throw and recovery frequency in games (r = -0.87 and confidence interval [CI] = 0.41; r = -0.90 and CI = 0.35; respectively). Oxygen consumption remained above baseline while blood lactate concentration remained unchanged during the games. The very likely correlation between anaerobic alactic contribution and action density (r = 0.95 and CI = 0.25) highlights the importance of the alactic metabolism. In general, our study demonstrates that goalball can be characterized as a high-intensity intermittent effort, where athlete performance is based on aerobic metabolism predominance while determinant actions are supplied by the anaerobic alactic metabolism. Specifically, higher values of LaB vs. GaM highlighted the need for standardization of specific protocols for goalball evaluation, mainly for the reproduction of ecologically valid values. In addition, peak oxygen consumption correlated with recovery frequency in the LaB condition, demonstrating that passive or low-intensity recovery between actions is fundamental to maintain performance.